Social Stratification in Mark Twai's The Prince and the Pauper Novel (1881):A Sociological Approach - Mulatsiwi, Oktri (2016)
This study is about Stratification. The problem of this study is how social stratification reflected in Mark Twain's The Prince and The Pauper novel. The object of this study is The Prince and The Pauper novel written by Mark Twain. It used sociological perspective. This study belongs to qualitative research. In this method, there are two types of data sources, namely primary and secondary data source. The primary data source is the novel and the secondary data source is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusion, based on the analysis it is clear that there is a close relation between this novel and social reality in America in the nineteenth century. Twain wants to criticize the case of stratification practices in America in the nineteenth century through The Prince and The Pauper novel. Keywords: Stratification, The Prince and the Pauper, Sociological perspective.